The Archaeology of Rural Affluence and Landscape Change at the Clemens Farmstead. (November 2013) - Groover, Mark D; Wolford, Tyler J
Abstract : During the 1820s, James and Sophia Clemens helped to establish Longtown, one of several farming communities settled by free persons of color in the Midwest. By the 1850s, James and Sophia were operating a prosperous farm in the Longtown community. The community was located along the Indiana and Ohio state line in Darke County, Ohio. The Clemens farm was atypical compared to other farms in Longtown. James Clemens was an economic outlier in the community, producing several times the average amount of crops and livestock compared to his neighbors during the mid-1800s. His home, a showplace, two-story, brick I-house that denoted rural success, was also unusual for the Longtown community. The example of the Clemens farm illustrates rural affluence expressed through production trends and the built environment among free persons of color in the Midwest. Landscape dynamics present in the 1800s are also illustrated by change that occurred to the house lot when the farm changed owners during the early twentieth century.